Worst month rain rate characterization for line-of-sight link performance in tropical locations (2021)
Communication equipment operating in the 30 to 300GHz frequencies avails large bandwidth and high speed data transmission but suffers greatly from attenuation by rain. The design of radio communication equipment has been based on predicted rain rate from the International Telecommunication Union-Radio (ITU-R) recommendations. This equipment fails in the tropics due to the differences in tropical and temperate rainfall structure on which the ITU-R recommendation is based. Five minutes rainfall data from two tropical locations in Nigeria – Jos (9.93 oN, 8.89oE, 1280 m) and Minna (9.61 oN, 6.56 oE, 223 m) were analysed. The 1- minute and ITU-R predicted rain rate (RR) were obtained with the Lavergnat and Gole model and MatLab rain rate statistics respectively while the logarithmic scale was used to convert the RR to exceedance time percentages (0.001 to 1%). The two parameter conversion factors, Q1 and β were generated with the ITU-R P. 841-6 recommendation; these were compared with the conversion factors recommended by ITU-R for global rain rate application. The results showed that at 0.01% exceedance, the ITU-R predicted rain rate for Jos and Minna were 87.1mm/hr and 91.6mm/hr respectively while the estimated rain rate from these locations were 84.5mm/hr and 110.0mm/hr respectively. The ITU-R conversion factor for the computation of the mean annual worst month from mean annual rain rate percentage exceedence were Q1 = 2.83 and β = - 0.15 while these parameters at Jos is, Q1 = 3.17 and β = - 0.19 and at Minna, Q1 = 3.12 and β = - 0.18. The results showed that there is a very strong relationship between the distribution of rain rate in the worst month and the annual rain rate distribution with coefficient of determination of 0.9994 and 0.9984 respectively. Thus for optimum link design budgeting, the modified values of Q and β should be adopted in these locations in order to enhance radio equipment performance in Nigeria.